EFEKTIVITAS KEBIJAKAN RESTORATIVE JUSTICE TERHADAP UPAYA PREFENTIF TINGKAT KEJAHATAN DI TABAGSEL - Siregar, Khoiruddin Manahan; Gunawan, Hendra (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This paper discusses how restorative justice is according to legal experts and the people of Tabagsel, and how it impacts preventive efforts on crime rates in South Tapanuli (Tabagsel). So to answer this problem, the author uses a qualitative method, which is to find out the impact of restorative justice in reducing crime rates or vice versa can increase crime rates.The findings from this study indicate that there are two impacts arising from this restorative justice, some are positive and some are negative. It has a negative form when RJ seems to make it easier for the law so that the perpetrators feel not afraid to commit the same crime, and vice versa has a positive impact when RJ creates intimacy between fellow perpetrators and victims so that they respect each other and are friends so they feel ashamed to do it again at another time.